2020
DOI: 10.33265/polar.v39.3614
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the extended Svalbard Airport monthly temperature series, and the compiled corresponding daily series 1898–2018

Abstract: The Svalbard Airport composite series spanning the period from 1898 to the present represents one of very few long-term instrumental temperature series from the High Arctic. A homogenized monthly temperature series is available since 2014. Here we increase the resolution from a monthly to daily basis, and further digitization of historical data has reduced the uncertainty of the series. The most pronounced changes in the 120-year record occur during the last three decades. For the 1991–2018 period the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 42 publications
5
82
0
Order By: Relevance
“…In higharctic and insular arctic food webs, it exploits both terrestrial and marine resources (Roth 2003, Ehrich et al 2015 and may therefore be affected by climate change through cascades in both food webs (Post et al 2009(Post et al , 2013. On the high-arctic Svalbard Archipelago, one of the fastestwarming locations on Earth (warming with an increase in annual ambient temperature of 3-5°C over the last 50 yr, Nordli et al 2020), rapidly increasing temperatures are causing drastic changes in both the marine and the terrestrial ecosystems (Descamps et al 2017). Spring sea ice in the fjords on the west coast of Svalbard provides arctic foxes with access to marine mammal prey and carrion Gjertz 1986, Hamilton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In higharctic and insular arctic food webs, it exploits both terrestrial and marine resources (Roth 2003, Ehrich et al 2015 and may therefore be affected by climate change through cascades in both food webs (Post et al 2009(Post et al , 2013. On the high-arctic Svalbard Archipelago, one of the fastestwarming locations on Earth (warming with an increase in annual ambient temperature of 3-5°C over the last 50 yr, Nordli et al 2020), rapidly increasing temperatures are causing drastic changes in both the marine and the terrestrial ecosystems (Descamps et al 2017). Spring sea ice in the fjords on the west coast of Svalbard provides arctic foxes with access to marine mammal prey and carrion Gjertz 1986, Hamilton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the time period 2016 to 2020, all records display negative MARST, which indicates permafrost conditions at all locations (Table 5). Svalbard lies in the continuous permafrost zone (Brown et al, 1997;Obu et al, 2019), and deep permafrost is observed in the area, e.g., within the abandoned mine shafts (Liestøl, 1977) and in boreholes (Christiansen et al, 2010). We found that the exposition of the rock wall only leads to small differences in MARST.…”
Section: The Influence Of Open Water and Sea Ice On Rstmentioning
confidence: 46%
“…The existing longest chronological series of SAT for Svalbard Airport and Bjørnøya, proved that contemporary warming is the most prominent climatic event in the Arctic since the beginning of the research period (Overland et al ., 2012; Nordli et al ., 2014, 2020; Gjelten et al ., 2016). Our study showed that at both stations, the ETCAW manifested in SON and DJF.…”
Section: Summary and Discussionmentioning
confidence: 99%